Current status of iridium-based complexes against lung cancer - Yang, Tongfu; Zhu, Minghui; Jiang, Ming; Yang, Feng; Zhang, Zhenlei (Frontiers in Pharmacology, 2022)
Lung cancer is one of the most common malignant tumors, with the highest mortality rate in the world, and its incidence is second only to breast cancer. It has posed a serious threat to human health. Cisplatin, a metal-based drug, is one of the most widely used chemotherapeutic agents for the treatment of various cancers. However, its clinical efficacy is seriously limited by numerous side effects and drug resistance. This has led to the exploration and development of other transition metal complexes for the treatment of malignant tumors. In recent years, iridium-based complexes have attracted extensive attention due to their potent anticancer activities, limited side effects, unique antitumor mechanisms, and rich optical properties, and are expected to be potential antitumor drugs. In this review, we summarize the recent progress of iridium complexes against lung cancer and introduce their anti-tumor mechanisms, including apoptosis, cycle arrest, inhibition of lung cancer cell migration, induction of immunogenic cell death, etc.